Cost-consequence analysis of two different active flowable hemostatic matrices in spine surgery patients. (3rd June 2017) - Makhija, D.; Rock, M.; Ikeme, S.; Kuntze, E.; Epstein, J. D.; Nicholson, G.; Price, J. S.; Patel, V.
Abstract: Objectives: A recently published retrospective analysis comparing two different active flowable hemostatic matrices (FLOSEAL and SURGIFLO Kit with Thrombin) showed significantly increased resource use and complications (surgery time, risk of blood product transfusion, and amount of matrix used) with SURGIFLO use compared to FLOSEAL in major spine surgery, and also significantly increased surgical time with SURGIFLO use in severe spine surgery. This analysis was developed as a follow-up to this prior analysis, to evaluate the cost-consequence of using FLOSEAL vs SURGIFLO in major and severe spine surgery. Methods: A cost consequence model was constructed from a US hospital provider perspective. Model parameters combined clinical inputs from the published retrospective analysis with supplemental analyses on annual spine surgery volume using the 2012 National Inpatient Sample (NIS) database. Cost of hemostatic matrices, blood product transfusion, and operating room time were identified from published literature. Various one-way and probabilistic sensitivity analyses were performed. Results: The base case for a medium volume hospital showed that, compared to SURGIFLO, patients receiving FLOSEAL required three fewer blood product transfusions and saved 27 h of OR time, resulting in annual savings of 151 per major and 574 per severe spine surgery. Additional scenarios for high and low volume hospitals supported cost savings in the base case. Probabilistic sensitivity analysis revealed FLOSEAL was cost-saving in 76% of simulations in major spine and 97% of iterations in severe spine surgery. Conclusions: This economic analysis indicates that use of FLOSEAL instead of SURGIFLO hemostatic matrices to induce hemostasis in both major and severe spine surgery could potentially lead to sizable cost savings in US hospitals, regardless of spinal surgery case-mix.